Study on the regulatory mechanisms of mitochondrial biosynthesis by polyoxometalates - Shan Lei; Bingnian Chen; Li Wang; Jian Li (Polyoxometalates)
In recent years, polyoxometalates (POMs) have been extensively researched for their potential in treating diabetes, tumors, cancer, inflammation, and other diseases, both in vitro and in vivo. Their primary therapeutic mechanisms are related to the generation of reactive oxygen species (ROS), leading to oxidative stress. Because mitochondria are the main site of ROS production, POM treatment mechanisms may be associated with mitochondrial biosynthesis. This study explores one of the mechanisms by which POMs impact diabetes mellitus, focusing on the increase in ROS and the resulting oxidative stress. Additionally, POMs have been preliminarily studied for their antioxidant and antitumor properties in the treatment of diabetes mellitus and tumors. The antioxidant and antitumor properties of POMs are promising for future therapeutic drugs. By examining oxidative stress and its impact on various biomolecules, POMs have been recognized as a drug therapy mechanism closely linked to mitochondria. Investigating the relationship between POMs and mitochondrial biosynthesis, as well as their impact on mitochondria, provides a basis for future in-depth studies on the role of POMs in treating tumors, diabetes, and other diseases.